Dai Perceptions of Chatgpt Use in The Production of Digital Dakwah Content in Cirebon - Mia Nurislamiah; Rirry Nissa Awliya; Widia Ningsih (Worldwide Research Publishing, 2025)
The wave of digital transformation that has pervaded nearly every aspect of human life in the twenty-first century carries implications that extend far beyond mere technological change. This shift reshapes the ways in which Muslims in Indonesia conduct dakwah (Islamic proselytisation), which has historically relied on face-to-face forums, religious study circles (majelis taklim), and Friday sermons. In the contemporary digital landscape, dakwah has evolved into digital content disseminated freely across platforms such as YouTube, Instagram, and TikTok, driven by the rapid growth of generative artificial intelligence most notably ChatGPT, launched by OpenAI in late 2022. This study examines the perceptions of dai (Islamic preachers) in Cirebon, West Java, toward the use of ChatGPT in the production of digital dakwah content, employing the Technology Acceptance Model (TAM) as its analytical framework. Using a descriptive qualitative approach with purposive sampling, data were gathered from five informants through in-depth interviews, observation, and documentation, and subsequently analysed using the Miles, Huberman, and Saldaña interactive model. Findings reveal that perceived usefulness is generally positive, particularly regarding content-production efficiency, whilst perceived ease of use varies substantially according to age and digital-literacy level. Three attitudinal typologies were identified: affirmative-pragmatic, critical-selective, and conservative-apprehensive, each grounded in distinct theological, epistemological, and ethical considerations. Behavioural intention to continue using ChatGPT is moderated by social norms within the religious community and the availability of institutional support.